Willy Loman In Bad-Faith: a Study of Death of a Salesman In Sartrean Terms: A Study of Willy Loman's Self-Deception in the Failure of the American Dream (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Arthur Miller was one of the leading Americanplaywrights of the twentieth century. Miller wrote Death of a Salesman, whichwon the Pulitzer Prize and transformed Miller into a national sensation. Manycritics described Death of a Salesman as the first great American tragedy, andMiller gained eminence as a man who understood the deep essence of the UnitedStates. Death of a Salesman was first produced on Broadway on Feb 10, 1949. Theplay has been studied generally in terms of a commentary on the failure of theAmerican Dream. Willy Loman has generally been regarded as a victim of theAmerican society. But this paper attempts to study Willy Loman’s character notas a victim either of American dream or of the society but as a man who himselfis responsible for his failure for not realizing his own nature as well as thenature of his dreams. He deceives himself and lives in ‘bad-faith’.